1992
DOI: 10.1038/eye.1992.49
|View full text |Cite
|
Sign up to set email alerts
|

Laser microsclerostomy for primary open angle glaucoma: A review of laser mechanisms and delivery systems

Abstract: SUMMARYA number of different lasers and delivery systems are currently used in experimental sclerostomy procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the initial studies on laser sclerostomy, ah interno or ah extano, involving animal eyes, blockage of the fistula by iris tissue prolapsing or by fibrin or cellular debris was a common complication in the early and intermediate term. 2 -4 There have been varying reports of closure of sclerostomy by iris tissue in procedures performed on Nd:Y AG peripheral iridectomy (8) Trabeculectomy (I): trabeculectomy + topical treatment (2) Trabeculectomy (2); trabeculectomy + topical treatment (1) Ocular massage + topical treatment (2) glaucoma patients. In an earlier series of 26 episodes of Holmium laser thermal sclerostomy ah extano studied by Hoskins et al '" iris incarceration was seen in all but 1 phakic patient but was a rare event in aphakic or pseudo phakic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial studies on laser sclerostomy, ah interno or ah extano, involving animal eyes, blockage of the fistula by iris tissue prolapsing or by fibrin or cellular debris was a common complication in the early and intermediate term. 2 -4 There have been varying reports of closure of sclerostomy by iris tissue in procedures performed on Nd:Y AG peripheral iridectomy (8) Trabeculectomy (I): trabeculectomy + topical treatment (2) Trabeculectomy (2); trabeculectomy + topical treatment (1) Ocular massage + topical treatment (2) glaucoma patients. In an earlier series of 26 episodes of Holmium laser thermal sclerostomy ah extano studied by Hoskins et al '" iris incarceration was seen in all but 1 phakic patient but was a rare event in aphakic or pseudo phakic patients.…”
Section: Discussionmentioning
confidence: 99%
“…While a gonio scopic delivery of laser energy overcomes this problem, it tends to be limited by technical difficulties. 1 An ab externo approach with specially designed probes, on the other hand, can help to reduce the extent of conjunctival dissec tion and keep the procedure quick and minimally invasive. THC:YAG (,Holmium') laser sclerostomy ab externo is the best known of the laser sclerostomies and recent reports have been encouraging.…”
mentioning
confidence: 99%
“…Various types of laser procedures have been introduced to simplify and improve glaucoma drainage surgery. Laser microsclerostomy has been performed ab interno [1] or ab externo using a holmium laser [10,11], erbium:YAG [12,26], excimer laser [2,5,22], or CO 2 laser [2,4,15,25]. Klink et al [14] reported deep sclerectomy in eyes of dead pigs using the erbium:YAG laser.…”
Section: Discussionmentioning
confidence: 99%